Water in the balance - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
Private irrigation in sub-Saharan Africa: Regional seminar on private sector participation and irrigation expansion in sub-Saharan Africa Proceedings of a seminar, Accra, Ghana, 2001, published by IWMI CTA FAO, 2002. 328 pp. ISBN 92 9090 494 1 CT